Maternal genetic link of a south Dravidian tribe with native Iranians indicating bidirectional migration - Charles Sylvester; Mysore Siddaiah Krishna; Jaya Sankar Rao; Adimoolam Chandrasekar (Taylor & Francis Group, 2019)
Background: The phylogeny of major mitochondrial DNA haplogroups has played a key role in assessing the people of India through molecular genetics. Aim: To resolve the phylogeny and phylogeographic pattern of autochthonous haplogroup R with its descendant haplogroup U in the Urali Kuruman tribal population of Southern India. Subjects and methods: Complete mitogenome sequences of 40 individuals were amplified and sequenced using the Sanger sequencing method. Mutations were scored referring to the revised Cambridge reference sequence, and phylogenetic trees were constructed using previously described sequences. Results: Novel sub-lineages of haplogroup R30: R30a1c1, and U1: U1a1c1d2, U1a1c1d2a were identified. Urali Kurumans pooled ancestry with the native Iranians sharing the sub-haplogroups R30a1c and U1a1c1d. The coalescence ages estimated for the sub-haplogroup R30a1c dates ∼ 9.4 ± 3.5 Kya and for subclade U1a1c1d dates ∼ 9.1 ± 2.7 Kya. Conclusion: The study revealed a genetic link between Iran and South Asia in the Neolithic time, indicating bidirectional migration and admixture.